Protocol for a 2-year longitudinal study of eating disturbances, mental health problems and overuse injuries in rock climbers (CLIMB) - Ulrika Tranaeus; Klara Edlund; Isabel Nigicser; Mikael Sansone; Fredrik Identeg; Henrik Hedelin; Niklas Forsberg (BMJ Open, 2023)
Introduction Rock climbing is a rapidly growing sport in which performance may be affected by participant’s weight and leanness, and there may be pressure on athletes with respect to their eating behaviour and body weight. However, there is sparse research performed on climbers, constituting a knowledge gap which the present study aims to fill. The primary outcomes of the study are to examine disordered eating and overuse injuries in rock climbers. Secondary variables are body image, indicators of relative energy deficiency, mental health problems, compulsive training, perfectionism, sleep quality and bone density.Method and analysis This prospective longitudinal study aims to recruit Swedish competitive rock climbers (>13 years) via the Swedish Climbing Federation. A non-athlete control group will be recruited via social media (n=equal of the climbing group). Data will be collected using streamlined validated web-based questionnaires with three follow-ups over 2 years. Inclusion criteria for rock climbers will be a minimum advanced level according to International Rock-Climbing Research Association. The non-athlete control group is matched for age and gender. Exclusion criteria are having competed at an elite level in any sport as well as training more often than twice per week. Statistical analyses will include multinominal logistic regression, multivariate analysis of variance (MANOVA) and structural equation modelling (SEM). We will assess effect measure modification when relevant and conduct sensitivity analyses to assess the impact of lost to follow-up.Ethics and dissemination The Rock-Climbers’ Longitudinal attitudes towards Injuries, Mental health and Body image study, CLIMB, was approved by the Swedish ethics authority (2021-05557-01). Results will be disseminated through peer-reviewed research papers, reports, research conferences, student theses and stakeholder communications.Trial registration number NCT05587270.